Conceptual bases for reforming the national health care system: to the formulation of principles - H. S. Stetsenko (Zaporozhye State Medical University, 2020)
The article is devoted to the problems of reforming domestic health care. First of all, what is worth paying attention to is the formulation of principles. Principles for public administration in the field of public health. The aim. Formulation and justification of principles on which the reform of domestic health care should take place. Materials and methods of research. The dialectical method was used to analyze the current state of domestic medicine. The system-structural method was used to analyze the public availability of care and to organize it was provision at the primary level. The introduction of compulsory health insurance in Ukraine was investigated using methods of analysis and synthesis. Results. Having extensive experience in the organization of public health protection both in Soviet times and in the conditions of independent Ukraine, the author states the following: public access to medical care consists in the possibility of equal access of citizens to the possibilities of medicine regardless of property or social situation, place of residence and the like. In the context of today's attention is focused: it is not about ensuring quality, comfort, namely the availability of medical care. The first two factors really depend first and foremost on the financial capabilities of the person, we are talking about accessibility here. And ensuring accessibility is a state task. Any state tries to promote it. It is argued that the fact that most patients receive medical care at the primary care level is not a secret. Focuses on the introduction of compulsory health insurance. Realities show that most of the world's leading countries have chosen this path in the organization of medical activities. The organizational and legal advantages of this type of insurance are undoubted. First of all, it is the introduction of contractual relations between the subjects of health insurance (patient, medical institution, insurance medical company, employer), changes in the system of financing the medical sphere, and improvement of control over the quality of rendering medical services. Conclusions. It is stated that the basic requirements for the principles of public health management should be: realism, complexity, and perspective.